Solanum lycopersicum cytokinin response factor (SlCRF) genes: characterization of CRF domain-containing ERF genes in tomato - Shi, Xiuling (Oxford University Press, 2012)
Cytokinin is an influential hormone in growth and developmental processes across many plant species. While several cytokinin-regulated genes have been well characterized in Arabidopsis, few have been identified in tomato, Solanum lycopersicum. Here a tomato family of 11 highly related cytokinin response factor genes designated as SlCRF1–SlCRF11 (Solanum lycopersicum cytokinin response factor) are identified and characterized. SlCRFs are AP2/ERF transcription factors and generally orthologous to Arabidopsis CRF clade members (AtCRFs). Some SlCRF genes lack a direct Arabidopsis orthologue and one SlCRF has a unique protein domain arrangement not seen in any other CRF protein. Expression analysis of SlCRF1–SlCRF11 revealed differential patterns and levels across plant tissues examined (leaf, stem, root and flower). Several SlCRFs show induction by cytokinin to various degrees, similar to AtCRFs. Additionally it is shown that some SlCRFs can be regulated by other factors, including NaCl, ethylene, methyl jasmonate, and salicylic acid. Examination of SlCRF proteins in transient Agrobacterium infiltration experiments indicates they can be nuclear localized in planta. Using a bimolecular fluorescence complementation (split-yellow fluorescent protein) system, it is also shown that SlCRF proteins can interact to form homo- and heterodimers. Overall this work indicates that some SlCRFs resemble previously identified CRFs in terms of structure, expression, and cytokinin regulation. However, SlCRFs have novel CRF protein forms and responses to abiotic factors, suggesting they may have a diverse set of roles in stress and hormone regulation in tomato.